Lack of Vacuolar H+ -Pyrophosphatase and Cytosolic Pyrophosphatases Causes Fatal Developmental Defects in Arabidopsis thaliana - Fukuda, Mayu; Mieda, Marika; Sato, Ryosuke; Kinoshita, Satoru; Tomoyama, Takaaki; Ferjani, Ali; Maeshima, Masayoshi; Segami, Shoji (Frontiers in Plant Science, 2020)
The cytosolic level of inorganic pyrophosphate (PPi) is finely regulated, with PPi hydrolyzed primarily by the vacuolar H+-pyrophosphatase (H+-PPase, VHP1/FUGU5/AVP1) and secondarily by five cytosolic soluble pyrophosphatases (sPPases; PPa1–PPa5) in Arabidopsis thaliana. Loss-of-function mutants of H+-PPase (fugu5s) have been reported to show atrophic phenotypes in their rosette leaves when nitrate is the sole nitrogen source in the culture medium. For this phenotype, two questions remain unanswered: why does atrophy depend on physical contact between shoots and the medium, and how does ammonium prevent such atrophy. To understand the mechanism driving this phenotype, we analyzed the growth and phenotypes of mutants on ammonium-free medium in detail. fugu5-1 showed cuticle defects, cell swelling, reduced β-glucan levels, and vein malformation in the leaves, suggesting cell wall weakening and cell lethality. Based on the observation in the double mutants fugu5-1 ppa1 and fugu5-1 ppa4 of more severe atrophy compared to fugu5-1, the nitrogen-dependent phenotype might be linked to PPi metabolism. To elucidate the role of ammonium in this process, we examined the fluctuations of sPPase mRNA levels and the possibility of alternative PPi-removing factors, such as other types of pyrophosphatase. First, we found that both the protein and mRNA levels of sPPases were unaffected by the nitrogen source. Second, to assess the influence of other PPi-removing factors, we examined the phenotypes of triple knockout mutants of H+-PPase and two sPPases on ammonium-containing medium. Both fugu5 ppa1 ppa2 and fugu5 ppa1 ppa4 had nearly lethal embryonic phenotypes, with the survivors showing striking dwarfism and abnormal morphology. Moreover, fugu5 ppa1+/– ppa4 showed severe atrophy at the leaf margins. The other triple mutants, fugu5 ppa1 ppa5 and fugu5 ppa2 ppa4, exhibited death of root hairs and were nearly sterile due to deformed pistils, respectively, even when grown on standard medium. Together, these results suggest that H+-PPase and sPPases act in concert to maintain PPi homeostasis, that the existence of other PPi removers is unlikely, and that ammonium may suppress the production of PPi during nitrogen metabolism rather than stimulating PPi hydrolysis.